2012
DOI: 10.1371/journal.pone.0052307
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of Combining Docetaxel (Taxotere) with the Antivascular Action of Ultrasound Stimulated Microbubbles

Abstract: Ultrasound stimulated microbubbles (USMB) are being investigated for their potential to promote the uptake of anticancer agents into tumor tissue by exploiting their ability to enhance microvascular permeability. At sufficiently high ultrasound transmit amplitudes it has also recently been shown that USMB treatments can, on their own, induce vascular damage, shutdown blood flow, and inhibit tumor growth. The objective of this study is to examine the antitumor effects of ‘antivascular’ USMB treatments in conjun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
99
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(123 citation statements)
references
References 69 publications
9
99
2
Order By: Relevance
“…As noted, for all animals the ratio of non-linear contrast before and after ACT treatment is close to 1 over the time window investigated demonstrating that that ACT does not affect tumor vascular blood flow on a global level in any marked manner. It has earlier been reported that high intensity US in combination with microbubbles can reduce perfusion [21]. Compared to the current study, however, in [21] significantly higher MI and longer US pulses were applied.…”
Section: In Vivo Imaging Of Activation and Deposition Of Act Bubblescontrasting
confidence: 65%
See 1 more Smart Citation
“…As noted, for all animals the ratio of non-linear contrast before and after ACT treatment is close to 1 over the time window investigated demonstrating that that ACT does not affect tumor vascular blood flow on a global level in any marked manner. It has earlier been reported that high intensity US in combination with microbubbles can reduce perfusion [21]. Compared to the current study, however, in [21] significantly higher MI and longer US pulses were applied.…”
Section: In Vivo Imaging Of Activation and Deposition Of Act Bubblescontrasting
confidence: 65%
“…It has earlier been reported that high intensity US in combination with microbubbles can reduce perfusion [21]. Compared to the current study, however, in [21] significantly higher MI and longer US pulses were applied. The lack of observed vascular effect shows that ACT treatment can be repeated several times in the same tumor.…”
Section: In Vivo Imaging Of Activation and Deposition Of Act Bubblescontrasting
confidence: 65%
“…However, in an effort to optimize biomechanical effects induced by Sonazoid™ microbubbles, the US Enhancement step for this group was performed by continuous insonation with 2.25 MHz and an MI of 0.4 for 5min and 45s. It is possible that this fairly strong and long regimen induce some kind of physiological response to shut down of the tumor vasculature, as has been reported elsewhere [24]. If so, this could prevent the drug penetrating tumor tissue and explain the lack of response in this group.…”
Section: Discussionmentioning
confidence: 64%
“…A subset of 5 animals were found dead one after day treatment, in which case they were included in the tumor growth data until that time point. Compared to similar studies [24], the number of unexplained fall outs are low in number, and these deaths are not considered to be treatment related. In the ACT+ABR group one animal, although its tumor was very small, was sacrificed in week 5 because of a necrotic tail at the ABR injection site.…”
Section: Groups Treatment Regimens and Responsesmentioning
confidence: 67%
“…The anti-vascular effect of USMB is promising and reproducible (5,10,11,28). It has been demonstrated that thermal, mechanical, such as cavitation and other non-linear mechanisms, and sonochemical effects are likely to contribute to the anti-vascular activities of microbubbles (7).…”
Section: Discussionmentioning
confidence: 99%